Reversible Medical Image Watermarking for Tamper Detection and Recovery - Liew, Siau-Chuin; Jasni, Mohamad Zain (IEEE, 2010)
This research paper discussed the usage of watermarking in medical images to ensure the authenticity and integrity of the image and reviewed some watermarking schemes that had been developed. A design of a reversible tamper detection and recovery watermarking scheme was then proposed. The watermarking scheme uses a 640x480x8 bits ultrasound grayscale image as a sample. The concept of ROI (Region Of Interest) and RONI (Region Of Non Interest) were applied. Watermark embedded can be used to detect tampering and recovery of the image can be done. The watermark is also reversible.